Three aspects of representation in neuroscience. Issue 11 (November 2022) - Baker, Ben; Lansdell, Benjamin; Kording, Konrad P.
Abstract : Neuroscientists often describe neural activity as a representation of something, or claim to have found evidence for a neural representation, but there is considerable ambiguity about what such claims entail. Here we develop a thorough account of what 'representation' does and should do for neuroscientists in terms of three key aspects of representation. (i) Correlation: a neural representation correlates to its represented content; (ii) causal role: the representation has a characteristic effect on behavior; and (iii) teleology: a goal or purpose served by the behavior and thus the representation. We draw broadly on literature in both neuroscience and philosophy to show how these three aspects are rooted in common approaches to understanding the brain and mind. We first describe different contexts that 'representation' has been closely linked to in neuroscience, then discuss each of the three aspects in detail. Highlights: Recent scientific discourse has pointed to challenges in the way the terms 'representation' and 'code' are commonly used in neuroscience. In neuroscience, one current line of thinking focuses on the kinds of representations formed in neural systems trained to predict incoming sensory inputs. Machine learning researchers are interested in how (artificial intelligence) AI can acquire representations of causal variables and representations that are disentangled. Philosophers work on questions about how representations relate to psychological explanation, to knowledge, and to phenomenological experiences. The best way to study neural representations and their impact on the mind and behavior is a multifaceted and interdisciplinary topic and we work here to build bridges between major sub-areas interested in this question.